Analisis Kemampuan Kognitif Siswa dalam Pembelajaran Akidah Akhlak di Madrasah Aliyah Al-Hikmah Soe Kelas X IPA - Kasim, Muhamad; Tamrin, Muhammad (Prodi Pendidikan Agama Islam, 2023)
This study aims to analyze the cognitive abilities of students in learning the moral principles of class X IPA MA Al-Hikmah Soe. researchers used a qualitative approach. The data collection techniques used are observation techniques, tests, interviews, and documentation. The results of this study indicate that the cognitive abilities of students in the learning process of Aqidah Akhlak in class X IPA MA Al-Hikmah Soe are in the very good category. This is based on the percentage level of student scores that are less than the KKM score, namely 72, on the cognitive test there are 4 people or 15.38% while as many as 22 people or 84.62% get grades above the passing standard of the moral creed subject. In this study the researchers also found that to improve students' cognitive abilities, the Madrasah carried out a program of activities outside the classroom to improve students' cognitive abilities, namely doing tahsin 10 minutes before entering the first learning hour, or guiding students to memorize asmaul husna. And subject teachers and homeroom teachers also carry out private guidance outside the classroom for students who have low cognitive abilities, in order to improve the students' cognitive abilitie.